Some regulatory matters matrimonial property. (Journal of actual problems of jurisprudence, 2016)
This article is devoted to questions of legal regulation of joint property of spouses. Currently,Kazakhstan has expanded the scope of property relations , especially in the transfer of rights to immovableproperty. Joint property of the spouses is any acquired by them during the marriage movable and immovable property. In connection with the mandatory registration of rights to immovable property andtransactions with it in practice, registration authorities, the question arose about the order of registration of the right of joint ownership of the spouses. The article describes the procedure of registration of rights,if the immovable property acquired in the name of one of the spouses.
Keywords: property; joint property of spouses; division of marital property; registration of rights to immovable property